2015
DOI: 10.3892/ol.2015.3489
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activator of nuclear factor κB expression is a prognostic factor in human osteosarcoma

Abstract: Abstract. Receptor activator of nuclear factor κB (RANK), a member of the tumour necrosis factor family, is activated by its ligand and regulates the differentiation of osteoclasts and dendritic cells. Local growth of osteosarcoma involves destruction of the host bone by osteoclasts and proteolytic mechanisms. Although the prognosis of patients with osteosarcoma has been improved by advances in chemotherapy over the last four decades, the issues of non-responders, and the lack of effective prognostic markers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…Bago-Horvath et al revealed that RANKL expression was significantly more common in osteosarcoma of the lower extremity than in any other location and did not find any significant correlation between RANKL and disease-free or osteosarcoma-specific survival. However, they did report that RANK expression is a negative prognostic factor regarding disease-free survival, confirming the data obtained by Trieb and Windehager [ 89 ]. Interestingly, in 2012, Papanastasiou et al [ 91 ] identified a new isoform of RANK (named RANK-c) generated by alternative splicing and expressed in breast cancer samples.…”
Section: Rank/rankl and Cancersupporting
confidence: 82%
See 2 more Smart Citations
“…Bago-Horvath et al revealed that RANKL expression was significantly more common in osteosarcoma of the lower extremity than in any other location and did not find any significant correlation between RANKL and disease-free or osteosarcoma-specific survival. However, they did report that RANK expression is a negative prognostic factor regarding disease-free survival, confirming the data obtained by Trieb and Windehager [ 89 ]. Interestingly, in 2012, Papanastasiou et al [ 91 ] identified a new isoform of RANK (named RANK-c) generated by alternative splicing and expressed in breast cancer samples.…”
Section: Rank/rankl and Cancersupporting
confidence: 82%
“…RANK expression was also described as being predictive of poor prognosis in bone metastatic patients but not in patients with visceral metastases [ 88 ]. Similarly, sarcoma cells also express RANK (18–69% depending on the series) [ 79 , 89 , 90 ] and expression is correlated with clinical parameters. Trieb and Windhager [ 89 ] described a reverse correlation between RANK expression and the overall survival of patients with osteosarcoma, but not with the response to chemotherapy.…”
Section: Rank/rankl and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, high RANK expression has been linked to a shorter PFS (p = 0.01) and OS (p = 0.02) in endometrial cancer [36]. RANK-positive osteosarcomas are also associated with higher mortality than RANKnegative cases (p < 0.05) [41]. A high RANKL expression has been associated with higher stage disease (p = 0.035) and a shorter OS (p = 0.008) in gastric cancer [37].…”
Section: The Rank-rankl Axis In Cancer Biologymentioning
confidence: 99%
“…The relative levels of RANK/RANKL/OPG expression may influence prognosis in numerous cancer types including breast, lung, endometrial, renal cell and gastric cancers, osteosarcoma and multiple myeloma (Fig. 4a, b) [34][35][36][37][38][39][40][41]. In breast cancer, microarray analysis demonstrated that low RANK and high OPG expression were associated with longer OS (p = 0.0078 and p = 0.034, respectively) and disease-free survival (p = 0.059 and p = 0.040, respectively) [34].…”
Section: The Rank-rankl Axis In Cancer Biologymentioning
confidence: 99%